The corporate takeover of the online public sphere: A critical examination, with reference to 'the New Zealand case' - Lincoln Dahlberg (Asia Pacific Network, 2005)
Much communications research is in agreement about the failure of mass media to adequately facilitate a public sphere of open and reflexive debate necessary for strong democratic culture. In contrast , the internet's decentralised, two-way communication is seen by many commentators to be extending such debate. However, there is some ambivalence among critical theorists as to the future role of the internet in advancing the public sphere. On the one hand, the internet is providing the means fot the voicing of positions and identities excluded from the mass media. On the other hand, a number of problem are limiting the extensiveness and effetivness of this voicing. One of the most significant problems is the corporate colonisation of cyberspace, and subsequent marginalisation rational-critical communication. It is this problem that i will focus on in this article, with reference to examples from what I refer to as the 'New Zealand online public sphere'. I show how online corporate portals and media sites are gaining the most attention orientated to public communication, including news, information, and discussion. These sites generally support conservative discourse and consumer practices. The result is a marginalisation online of the very voices marginalised offline, and also of the critical-reflexive form of communication that makes for a strong public sphere. I conclude by noting that corporate colonisation is as yet only partial, and control of attention and media is highly contested by multiple 'alternative' discursive spaces online.